The Routledge handbook of gender in Central-Eastern Europe and Eurasia
1 online resource (xxxii, 554 pages)
Keywords: "This Handbook is the key reference for contemporary historical and political approaches to gender in Central-Eastern Europe and Eurasia. Leading scholars examine the region's highly diverse politics, histories, cultures, ethnicities, and religions, and how these structures intersect with gender alongside class, sexuality, coloniality, and racism. Comprising 50 chapters, the Handbook is divided into six thematic parts: Part 1 Conceptual Debates and Methodological Differences Part 2 Feminist and Women's Movements Cooperating and Colliding Part 3 Constructions of Gender in Different Ideologies Part 4 Lived Experience of the Individual in Different Regimes Part 5 The Ambiguous Postcommunist Transitions Part 6 Postcommunist Policy Issues With a focus on defining debates, the collection considers how the shared experiences, especially communism, affect political forces' organization of gender through a broad variety of topics including feminisms, ideology, violence, independence, regime transition, and public policy. It is a foundational collection that will become invaluable to scholars and students across a range of disciplines including Women's, Gender, and Sexuality Studies and Central-Eastern Europe and Eurasian Studies"--